A SYSTEMATIC LITERATURE REVIEW OF FACTORS INFLUENCING SOCIAL ENTREPRENEURIAL INTENTIONS - Shih-Yee Loh; Jeffrey Cheah (Journal of Islamic, Social, Economics and Development, 2022)
Social entrepreneurship movement has proven its efficiency in addressing worldpressing social issues immediately upon creating economic value. However, social enterprisedevelopment in many countries, including Malaysia, is still at the infancy stage. This paperdesigned to identify and conceptually structure the most prominent factors that influence thesocial entrepreneurial intentions, based on the systematic review process, content analysis andgap analysis approaches. Specifically, from 967 records derived from renowned scholarlydatabase Scopus, this study deliberately stipulated 17 core empirical literature, inspected within-depth content analysis to identify the most prevalence constructs employed by previousresearchers, and mapped their statistical findings by gap analysis approach. Subsequently,grounded on the Theory of Planned Behaviour, a conceptual framework that posits socialentrepreneurial intention, which comprises of perceived social support, moral obligation,selfefficacy, empathy and social worth, was established. The research findings deliberatelycontribute to social enterprise literature in a developing country context which remains limited,offers a guideline to a relevant legal agency in enhancing the social enterprise ecosystem, andprovide a practical reference to future research by disclosing the research gaps and areadymade model for empirical research.